Anti-NMDA receptor encephalitis - A. V. Surovtseva (Rossijskij Vestnik Perinatologii i Pediatrii, 2016)
Anti-N-methyl-D-aspartate (anti-NMDA) receptor encephalitis is an autoimmune central nervous system disease mediated by antibodies to certain subunit of the N-methyl-D-aspartate receptor and characterized by the development of severe psychiatric and neurological disorders in previously healthy children. The paper describes a clinical case in an 8-year-old female patient with this disease presenting with seizures, psychiatric symptoms and behavioral problems. Then the disease progressed to dyskinesis and memory and speech disorders. The final diagnosis of anti-NMDA receptor encephalitis was made after identifying anti-NMDA receptor antibodies in the cerebral spinal fluid.